Breeding activities of ingerophrynus parvus(Anura: Bufonidae) in Kedah, Malaysia - Shahriza, S; Ibrahim, J; Shahrul Anuar, M.S (Universiti Kebangsaan Malaysia, 2012)
The breeding activities of the Dwarf toad, Ingerophrynus parvus were observed under natural conditions at Sungai Junjong, Kulim, Kedah, Peninsular Malaysia for a period of 12 months. Breeding parameters, such as calling activities, amplecant pairs, eggs deposition and presence of tadpoles were examined every week in each month. Pearson correlation was used to analyse the relationship between rainfall and each breeding parameter. The results showed positive relationships between rainfall and calling activities (r=0.74), between rainfall and amplexus activities (r=0.52), and between rainfall and spawning activities (0.81).